CONSIDERATIONS ON THE PROPHYLAXIS OF SEVERE FORMS OF COVID-19 THROUGH ENDURANCE EXERCISES - Bogdan-Alexandru HAGIU (Cluj University Press, 2022)
Prophylaxis of severe forms of COVID-19 can be achieved by combating sedentary lifestyle, preferably through moderate intensity endurance exercises, dosed so as not to cause immune disorders. The mechanism is likely to be to protect the mitochondria from oxidative stress. The anti-inflammatory effects may also occur in the organs affected by the virus. The high intensity of the effort (interval training or resistance training) can promote, in addition to immune disorders, even the penetration of the virus into the target cells (according to a hypothesis to be confirmed by future studies). However, there are preliminary results according to which some high-intensity exercises can be adapted to avoid hypoxia and thus be used for COVID-19 prophylaxis. Prevention of serious complications of SARSCOV-2 infection through exercise may be of interest to obese, diabetic and the elderly, high-risk categories.   REZUMAT. Considerații privind profilaxia formelor severe de covid-19 prin exerciții de anduranță. Profilaxia formelor severe de COVID-19 se poate realiza prin combaterea sedentarismului, de preferință prin exerciții de anduranță de intensitate moderată, dozate astfel încât să nu provoace tulburări imunitare. Este posibil ca mecanismul să fie protejarea mitocondriilor de stresul oxidativ. Se poate ca efectele antiinflamatoare să se manifeste inclusiv în organele afectate de respectivul virus. Intensitatea mare a efortului (antrenament pe intervale sau antrenament cu rezistență) poate favoriza, pe lângă tulburările imunitare, chiar și pătrunderea virusului în celulele țintă (conform unei ipoteze ce urmează a fi confirmată de studii viitoare). Există însă rezultate preliminare conform cărora și unele exerciții de intensitate mare pot fi adaptate în sensul evitării hipoxiei și astfel să fie folosite pentru profilaxia COVID-19. Prevenirea complicațiilor grave ale infecției cu SARSCOV-2 prin exerciții fizice poate fi de interes pentru categoriile cu risc ridicat: obezi, diabetici și vârstnici. Cuvinte cheie: COVID-19, exerciții, mitocondrii Received: 2021 November 1; Revised: 2022 January 09; Accepted: 2022 January 10; Available online: 2022 May 5; Available print: 2022 May 30.